2016
DOI: 10.1097/md.0000000000005212
|View full text |Cite
|
Sign up to set email alerts
|

Is surgery indicated for elderly patients with early stage nonsmall cell lung cancer, in the era of stereotactic body radiotherapy?

Abstract: Background:The aim of this article is to assess the influence of comorbidities among elderly patients (at least 70 year old) undergoing surgery for early stage nonsmall cell lung cancer (NSCLC) and to explore the tolerability and efficacy of surgery in relation to stereotactic body radiotherapy (SBRT) in this patient population.Methods:A review of the literature on the prevalence of comorbidities among elderly patients with early stage NSCLC, and the impact of comorbidity factors on survival following surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…While historically it may be true, radiation oncology has evolved significantly over the past 20 years due to advances in imaging and radiotherapy techniques. This allows precise targeting of the tumor to a high dose and thus potential cure despite the presence of multiple co-morbidity factors [6]. As a result, radiation oncologists often face difficult treatment decisions on how to provide the best treatment to a growing segment of the population when they have to strike a delicate balance of choosing between treatment toxicity versus potential cure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While historically it may be true, radiation oncology has evolved significantly over the past 20 years due to advances in imaging and radiotherapy techniques. This allows precise targeting of the tumor to a high dose and thus potential cure despite the presence of multiple co-morbidity factors [6]. As a result, radiation oncologists often face difficult treatment decisions on how to provide the best treatment to a growing segment of the population when they have to strike a delicate balance of choosing between treatment toxicity versus potential cure.…”
Section: Introductionmentioning
confidence: 99%
“…A course of curative radiotherapy may last for six to eight weeks and may potentially affect an older patient’s quality of life (QOL) because of their limited mobility [11,12]. Those issues need to be addressed to provide potential solutions which may improve quality of care for older cancer patients, such as hypofractionated and stereotactic body radiation [6,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the disease with the highest morbidity and mortality rate in the world 1. In 2017, it has been estimated that lung cancer will account for 13% of all new cancer cases and for 26% of cancer‐related deaths 2.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 13 ] It utilized advanced imaging techniques to deliver a targeted radiation dose to a tumor with a high degree of precision and steep dose gradients. [ 9 10 ] Additionally, it can also minimize the dose to normal tissues, which can help preserve the healthy tissue for patients with lung cancer. It has been reported that IGSBR for the treatment of lung cancer achieved excellent effect of local control rates for primary tumors, and metastatic malignancies.…”
Section: Introductionmentioning
confidence: 99%